HUBUNGAN PENGETAHUAN MAKANAN DAN KESEHATAN DENGAN FREKUENSI KONSUMSI MAKANAN JAJANAN PADA ANAK SEKOLAH DASAR PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Amelia, Kindi; yuliana, yuliana; kasmita, kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The purpose of this research was to analyze relationship between food andhealth knowledge with food consumption frequency for elementary schoolstudents in SD Pembangunan Laboratorium UNP. This research was descriptivecorrelation. Population in this research was 75 students from IV, V, and VI classin SD Pembangunan Laboratorium UNP. Based on the result it was shows that thehighest percentage of student who has knowledge about food and health was infair category (44%). From the frequency of food consumption, the highestpercentage of student consumption is nugget (56%), while roasted meatball(55%), noodle sausage (54%), pempek (53%), and batagor (50%). The result alsoshows negative relationship between food and health knowledge withconsumption frequency of snack for elementary school students in SDPembangunan Laboratorium UNP. It is mean that the highest knowledge thatstudent have, the lesser frequency student to consume snack in SD PembangunanLaboratorium UNP.Keywords: knowledge, consumption frequency, food and health.